Subjective Vitality and Its Relationship with Self Presentation Strategies Among Damascus University Students with Special Needs A Field Study - الجهني, ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research to acknowledge the biological self-level and self-representation strategies in a sample from Damascus University from the colleges that have special needs students and the colleges chosen were (Sharia, Pedagogy, literature) and defining the connection between self-vitality and self-representation strategies in the sample of Damascus University students. Also differentiating between the average mark of this sample on the self-immunity according to the following variables (sex, major) for this reason the researcher chose a sample consisting of 100 students, and the standard used was the self-vitality standard that was prepared by Abdulrahman 2022 and self-representation strategy standard presented by Lee and others in 1999. The most important results gleaned from this research is: The sample showed an average to high on the self-vitality scale. The results also showed that there is a positive connection between self-vitality and assertive self-representation strategies, and there weren’t any differences between the degree of self-vitality according to sex or major.